2016
DOI: 10.1161/circep.116.004346
|View full text |Cite
|
Sign up to set email alerts
|

Longer Left Ventricular Electric Delay Reduces Mitral Regurgitation After Cardiac Resynchronization Therapy

Abstract: Background-Mitral regurgitation (MR) is associated with worse survival in those undergoing cardiac resynchronization therapy (CRT). Left ventricular (LV) lead position in CRT may ameliorate mechanisms of MR. We examine the association between a longer LV electric delay (QLV) at the LV stimulation site and MR reduction after CRT. Methods and Results-QLV was assessed retrospectively in 426 patients enrolled in the SMART-AV study (SmartDelay Determined AV Optimization: A Comparison to Other AV Delay Methods Used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…There has been growing interest in the utilisation of electrical parameters for LV lead placement. Retrospective analysis of the SMART-AV trial suggested that prolonged QLV was a predictor of superior response in terms of reduction in mitral regurgitation 6 months post-implant and improvement in echocardiographic remodelling measures at 3 months [18]. A similar retrospective analysis of a single-centre study's CRT database over nine years also showed a similar association between prolonged QLVs and predicting heart failure hospitalisation and mortality [19].…”
Section: The Evidence For Targeting the Area Of Latest Electrical Act...mentioning
confidence: 86%
“…There has been growing interest in the utilisation of electrical parameters for LV lead placement. Retrospective analysis of the SMART-AV trial suggested that prolonged QLV was a predictor of superior response in terms of reduction in mitral regurgitation 6 months post-implant and improvement in echocardiographic remodelling measures at 3 months [18]. A similar retrospective analysis of a single-centre study's CRT database over nine years also showed a similar association between prolonged QLVs and predicting heart failure hospitalisation and mortality [19].…”
Section: The Evidence For Targeting the Area Of Latest Electrical Act...mentioning
confidence: 86%
“…Optimized delays are demonstrated by mitral inflow velocity or LVOT VTI, which are obtained by Doppler echocardiography (Gorcsan et al, 2008; Jansen et al, 2006; Trifunović et al, 2009; Waggoner et al, 2008). The ideal LVOT delay shows maximum VTI upon programming, and the ideal AV delay shows E and A waves on transmitral inflow Doppler signals (Chatterjee et al, 2016). This modality has several advantages, including its noninvasive character, precision, and good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Management of patients with HF and severe FMR consists of optimizing medical therapy as first line therapy. Furthermore GDMT and cardiac resynchronization therapy may improve FMR and preclude the need for an invasive TEER procedure [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%